Salmonella paratyphi spondylitis: a case report - Kumar, Pradeep (Springer-Verlag, 2007)
This is a case report of acute L3/4 vertebral osteomyelitis due to Salmonella paratyphi A confirmed by culture from vertebral needle biopsy. From a review of the literature this is the first reported case with bacteriological confirmation. The rarity of Salmonella paratyphi spondylitis and the options for treatment are discussed.